2008
DOI: 10.1161/hypertensionaha.108.111625
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoadrenal Stress Reactivity Is a Predictor of Future Blood Pressure

Abstract: Abstract-In the present study we hypothesized that arterial catecholamine concentrations during rest and 2 laboratory stress tests were independent predictors of blood pressure at an 18-year follow-up. At entry, blood pressure, heart rate, and arterial plasma epinephrine and norepinephrine concentrations were measured in 99 healthy men (age: 19.3Ϯ0.4 years, meanϮSD) at rest, during a mental arithmetic test, and during a cold pressor test. After 18.0Ϯ0.9 years of follow-up, resting blood pressure was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(96 citation statements)
references
References 45 publications
5
83
2
3
Order By: Relevance
“…Interestingly, a previous report on the basis of the same material as that presented in this article found that systolic BP, epinephrine, and norepinephrine responses to MST substantially increased the possibility to predict resting BP 18 years later. 9 Moreover, absolute responses at the initial examination increased the prediction of BP more than ⌬ responses. This indicates that absolute responses during stress may be superior to ⌬ responses when assessing stress reactivity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, a previous report on the basis of the same material as that presented in this article found that systolic BP, epinephrine, and norepinephrine responses to MST substantially increased the possibility to predict resting BP 18 years later. 9 Moreover, absolute responses at the initial examination increased the prediction of BP more than ⌬ responses. This indicates that absolute responses during stress may be superior to ⌬ responses when assessing stress reactivity.…”
Section: Discussionmentioning
confidence: 98%
“…This selection was initially done to ensure a satisfying BP range for the purpose of assessing whether screening BP was related to sympathetic function and coronary risk factors. 9 All were white except 1 who was half Asian. They were previously healthy without any history of diabetes mellitus, renal disease, increased BP, or other CV diseases, including a normal physical examination, ECG, routine blood tests, and urine analysis.…”
Section: Participantsmentioning
confidence: 99%
“…All subjects recruited from sources other than the follow-up study had to go through a thorough screening procedure, including past medical history, medications, clinical examination, routine blood and urine samples, and BP obtained by a trained physician or nurse according to procedures from the follow-up study. 8 We included participants between 35 and 51 years of age, with resting office systolic BP of 4140 and/or diastolic BP 490 mm Hg or daytime average BP of more than 135/85 mm Hg if they had recently undergone a 24-h ambulatory BP recording. Subjects with diabetes mellitus, CVD, renal disease, or screening BP 4180/110 mm Hg, or subjects using antihypertensive, anticoagulative, antiplatelet or cholesterollowering medication were excluded.…”
Section: Participantsmentioning
confidence: 99%
“…This is the first double-blind randomized crossover study assessing whether high intakes of relatively pure anthocyanins can reduce BP and alter BP regulatory mechanisms in subjects with a high normal BP. We have previously shown that cardiovascular and catecholamine reactivity to mental stress predict BP after 18 years, 8 and it has been suggested that increased stress reactivity per se has a role in the development of hypertension and CVD. 9 Moreover, various antioxidants have been shown to attenuate BP responses to both cold pressor test (CPT) 10 and mental stress test (MST), 11 alleviate perceived stress and post-task cortisol levels after MST 12 and alter the sympathetic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Its pathophysiology is complex and involves genetic, environmental and behavioral factors that make individuals susceptible to the development thereof. The cold test, an experimental human stress induction technique used for the first time by Hines and Brown in 1936, would predict the onset of hypertension [4] [5]. By identifying individuals at risk of having a HBP, we can carry out preventive activities which would be beneficial not only to the patient but also to the public health.…”
Section: Introductionmentioning
confidence: 99%